Technical efficiency impact of microfinance on small scale resettled sugar cane farmers in Zimbabwe - Simion Matsvai; Abbissynia Mushunje; Simbarashe Tatsvarei (Cogent Economics & Finance, 2022)
The main objective of the study was to investigate the impact of microfinance on smallholder resettled sugarcane farmers' productivity and technical efficiency. The study evaluated the impact of microfinance on technical efficiency of resettled sugarcane smallholders as well as the determinants of their technical efficiency. The study used Transcendental Logarithmic (Translog) Stochastic Frontier Analysis. Data from a household level survey of 2018 was collected using questionnaires in a multi-stage sampling technique. The hypothesis tests confirmed the adequacy of Translog SFA frontier over Cobb-Douglas together with the appropriateness of SFA over OLS. The results revealed that both microfinance and intensity of participation significantly improve technical efficiency. Extension services, secondary education, tertiary education, experience, and farming assets were among statistically significant determinants of observed variation in technical efficiency. Estimated technical efficiency scores from the truncated normal distribution model with heteroscedasticity and exogenous determinants were on average 64.4% and 33.6% for treatment and control groups, respectively. Bank participants were more efficient (65.4%) than MFIs participants (63.3%). The results confirmed that microfinance promote efficient utilization of agricultural inputs. Policy suggestions include expansion and sufficient disbursement of microfinance.
Keywords: 330; microfinance; technical efficiency; resettled sugarcane farmers